ANALISIS KEEFEKTIFAN PROGRAM JENDELA LITERASI KITA DI SDN SERANG 13 - Amsanah; Mahdiyah; Ryan Pratiwa Putra; B. Herawan Hayadi; Mutoharoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This research was motivated by the low literacy achievement in the Education Report of SDN Serang 13, which requires targeted intervention. The main objective of the study was to analyze the effectiveness of the implementation of the